Insulin-Like Growth Factor 1 Receptor Deficiency in Macrophages Accelerates Atherosclerosis and Induces an Unstable Plaque Phenotype in Apolipoprotein E Deficient Mice - Higashi, Yusuke (Circulation, 2016)
BACKGROUND: We have previously shown that systemic infusion of insulin-like growth factor-1 (IGF-1) exerts anti-inflammatory and anti-oxidant effects and reduces atherosclerotic burden in apolipoprotein E (Apoe) deficient mice. Monocytes/macrophages express high levels of IGF-1 receptor (IGF1R) and play a pivotal role in atherogenesis but the potential effects of IGF-1 on their function are unknown. METHODS AND RESULTS: To determine mechanisms whereby IGF-1 reduces atherosclerosis and to explore the potential involvement of monocytes/macrophages, we created monocyte/ macrophage specific IGF1R knockout (MΦ-IGF1R-KO) mice on Apoe(−/−) background. We assessed atherosclerotic burden, plaque features of stability, and monocyte recruitment to atherosclerotic lesions. Phenotypic changes of IGF1R-deficient macrophages were investigated in culture. MΦ-IGF1R-KO significantly increased atherosclerotic lesion formation, as assessed by Oil-red-O staining of en face aortae and aortic root cross-sections, and changed plaque composition to a less stable phenotype, characterized by increased macrophage and decreased α-smooth muscle actin-positive cell population, fibrous cap thinning, and decreased collagen content. Brachiocephalic artery lesions of MΦ-IGF1R-KO mice had histological features implying plaque vulnerability. Macrophages isolated from MΦ-IGF1R-KO mice showed enhanced proinflammatory responses upon stimulation by IFNγ and oxidized LDL and elevated antioxidant gene expression levels. Moreover, IGF1R deficient macrophages had decreased expression of ABCA1 and ABCG1 and reduced lipid efflux. CONCLUSIONS: Our data indicate that macrophage IGF1R signaling suppresses macrophage and foam cell accumulation in lesions and reduces plaque vulnerability, providing a novel mechanism whereby IGF-1 exerts anti-atherogenic effects.